Causality of genetically determined glucosamine supplementation on cognition and sarcopenia: a Mendelian randomization study - Kang, Yi; Tang, Yidan; Kong, Weishuang; Zhu, Tao; Chen, Guo (Frontiers in Endocrinology, 2024)
BackgroundEvidence indicates a negative link between glucosamine and age-related cognitive decline and sarcopenia. However, the causal relationship remains uncertain. This study aims to verify whether glucosamine is causally associated with cognitive function and sarcopenia.MethodForty-eight genetic variants linked to glucosamine use were extracted from the MRC-IEU consortium. Besides, we gathered cognition proxy indicators [cognitive performance and fluid intelligence score (FIS)], and sarcopenia-related indicators, namely, appendicular lean mass (ALM), whole body fat-free mass (WBFM), low hand grip strength, facial aging (FA), moderate to vigorous physical activity levels, usual walking pace and DNA methylation GrimAge acceleration from the large publicly available genome-wide association studies. Initially, Mendelian randomization (MR) analyses were conducted to ascertain the causal impact of glucosamine on cognition and sarcopenia-related traits. Subsequently, the two-step MR and multivariable MR (MVMR) were employed to examine whether any mediators causally mediated the observed associations.ResultMR analysis indicated that glucosamine was associated with increased cognitive performance (p = 8.46E-04), FIS (p = 7.50E-04), ALM (p = 6.45E-08), WBFM (p = 1.97E-03), usual walking pace (p = 2.55E-07), and moderate to vigorous physical activity levels (p = 3.29E-03), but associated with decreased FA risk (p = 3.77E-05) and DNA methylation GrimAge acceleration (p = 0.001). However, there were no significant causal associations between glucosamine and low hand grip strength. Multivariable MR showed that glucosamine continued to have a significant effect on cognitive performance, FIS, ALM, WBFM, usual walking pace, and moderate to vigorous physical activity levels after controlling for osteoarthritis (OA) and body mass index (BMI) (p < 0.05). We further found that C-reactive protein levels (CRP) may mediate the association of glucosamine and ALM, WBFM, usual walking pace, and physical activity (p < 0.05), and basal metabolic rate (BMR) may mediate the association of glucosamine and cognitive performance, FIS, ALM, WBFM, and usual walking pace (p < 0.05).ConclusionRegular glucosamine use enhances cognitive function and postpones sarcopenia for preserving the functional capacities necessary, and the impact of glucosamine on cognition and sarcopenia could be partially attributed to the mediation of BMR and CRP.